O papel das imagens nos processos de comunicação: ações do corpo, ações no corpo - Machado, Adriana Bittencourt (2007)
The place of image in communication processes constitutes the initial ignition point for the research herein presented. For this study it became clearly necessary to treat image as a specific type of information that has transitoriness as a central feature. Proposing that all communication is based in or assumes transformation, we can see that it brings an evolutionary tendency to its domains, which allows a comprehension of how images may operate for communication to take place. For this purpose it became necessary to investigate the conditions that make communication between the human body and the environment not just possible but, most importantly, efficient. To this end, it became indispensable to treat body and environment as phenomena immersed in co-evolutionary processes. Here the body is thought of as media, as in the Bodymedia Theory of Katz and Greiner, that claims that the body is not an information processor, but is rather a medium of itself. Its exchanges with the environment are provisional and circumstantial. The communication that the body makes or does is always that of the collection of information that constitute it. Based on this concept of the body, the hypothesis of this dissertation is that the image constitutes itself in the basic materiality of communication processes which operate whenever human bodies are involved. The body is image in flow, in time. As such, the body is not merely image in movement. The image is, overall, one of the possible modes of its communication. This dissertation does not treat image as a type of photographic register of the real; its objective is to sustain that the images of the body are processual and indexes of its time, and to do this, an inter-theory reduction was applied that allows a dialogue between the semiotics of Charles Sanders Peirce and Darwin s theory of evolution